1991
DOI: 10.2136/sssaj1991.03615995005500060031x
|View full text |Cite
|
Sign up to set email alerts
|

Canopy and Soil Modification of Precipitation Chemistry in a Temperate Rain Forest

Abstract: Little is known about the chemistry of solutions moving through old‐growth coastal temperate coniferous rain forests. The major objectives of this study were to examine precipitation, throughfall, stemflow, and soil solution chemistry in an old‐growth temperate rain forest in the Hoh River valley on the northwest Washington coast 32 km from the Pacific Ocean, and to determine mechanisms involved with changes in solution chemistry. Dominant species were Douglas‐fir (Pseudotsuga menziesii [Mirb.] Franco), wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 0 publications
1
40
0
Order By: Relevance
“…Linear regression of the relationship between cation sum vs. the anion sum showed an r 2 = 0.95 and slope of 0.95 (Figure 2a,b). Edmonds et al (1991) [45] suggested that anion deficit means of the amount of unmeasured organic acids. Kim et al (2013) [32] found that the organic acids (CH3COO …”
Section: Quality Assurancementioning
confidence: 99%
“…Linear regression of the relationship between cation sum vs. the anion sum showed an r 2 = 0.95 and slope of 0.95 (Figure 2a,b). Edmonds et al (1991) [45] suggested that anion deficit means of the amount of unmeasured organic acids. Kim et al (2013) [32] found that the organic acids (CH3COO …”
Section: Quality Assurancementioning
confidence: 99%
“…Presumably, the environment is selecting for a more depauperate microbial composition than the source materials. For example, the acidic nature of aboveground biomass means that there may be many organisms that cannot tolerate well the constantly buffered carbonate reservoir below ground (Alban, 1969;Turner & Franz, 1985;Edmonds et al, 1991). The degree to which subsequent evolutionary development of unique caveadapted strains has progressed could be used as some indication of the age of the cave and time since it was first microbially colonized.…”
Section: Microbial Considerationsmentioning
confidence: 99%
“…Although canopy-atmosphere interactions have been reported in temperate forests [1,5,14,29,42], few or limited number of the studies on canopy exchange processes have been conducted in Chinese forests recently, particularly in subtropical forests [18,25,26].…”
Section: Introductionmentioning
confidence: 99%